LED-Based Light Source Combined with Quantum Dot for Spectral Imaging. (20th May 2019) - Bae, Young Min; Kang, Dong-Goo; Shin, Ki Young; Lee, Wonju; Yoo, Dong-Wook
Abstract : Quantum dot (QD) is a kind of semiconductor nanoparticle and shows photoluminescence, in which the light with narrow spectral band is emitted from the QD after the absorption of the excitation light. In this study, it is demonstrated that the LED-based light source combined with a QD film can be applied to spectral imaging. The polymer film with QD was prepared by photopolymerization. Through measurement of the emission spectrum, it was confirmed that the optical intensity at the peak wavelength of the spectral bands of 410 and 540 nm could be controlled by changing the thickness of the film. In the study using a home-made phantom mimicking blood vessels, the patterns' contrast in the phantom images could be enhanced by using LED combined with QD as compared with the white light image. The LED light combined with the QD film provides a useful solution for illumination for spectral imaging.